Praktik Fraud Dalam Perspektif Novel “Negeri Para Bedebah” Karya Tere Liye. - Oktavian Yafi Subikda; Reza Shah Fahrezi; Eva Dwi Kurniawan (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research explores the representation of bribery and window dressing practices in the novel "Negeri Para Bedebah" and its relevance to audit and accounting theories. Thomas, the main character, engages in fraudulent activities by bribing and manipulating financial reports to save Bank Semesta. Bribery involves risking one-third of customer savings to influence the central bank to approve the acquisition. The practice of window dressing is also revealed in the attempt to acquire and merge four small banks. The central bank is involved in covering up data to create a positive impression of Bank Semesta's financial health. This research contributes to the understanding of audit and accounting theories and provides new insights into fraud prevention and detection.